2015
DOI: 10.1245/s10434-015-4471-x
|View full text |Cite
|
Sign up to set email alerts
|

Octreoscan Versus FDG-PET for Neuroendocrine Tumor Staging: A Biological Approach

Abstract: Tumor differentiation can be used to guide selection of nuclear imaging modalities for staging gastrointestinal and pancreatic NETs. Octreoscan appears more sensitive than (18)FDG-PET for well-differentiated NETs, whereas (18)FDG-PET demonstrates superior sensitivity for poorly-differentiated NETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 26 publications
0
65
0
Order By: Relevance
“…In particular, OCT appears more sensitive than 18 F-FDG for well-differentiated tumors, whereas 18 F-FDG demonstrates superior sensitivity for undifferentiated lesions [57]. In this sense, being patients positive at 18 F-FDG inoperable, there is no role for RGS with 18 F-FDG in patients with NETs.…”
Section: Reviewmentioning
confidence: 98%
“…In particular, OCT appears more sensitive than 18 F-FDG for well-differentiated tumors, whereas 18 F-FDG demonstrates superior sensitivity for undifferentiated lesions [57]. In this sense, being patients positive at 18 F-FDG inoperable, there is no role for RGS with 18 F-FDG in patients with NETs.…”
Section: Reviewmentioning
confidence: 98%
“…However, given that these tumors frequently overexpress SSTR2, they often clinically respond to synthetic somatostatin analogs such as octreotide and lanreotide (16)(17)(18)(19). Indeed, diagnostic imaging studies of SSTR targets are standard for so-called "octreotide-avid" tumors (20), and peptidebased receptor radionuclide therapy also has been used to clinical effect (21). Thus, we reasoned that octreotide-targeted cellular transduction would enable the expression of tumor necrosis factor (TNF) within the SSTR2-expressing tumor cells after systemic administration through the vulnerable tumor-associated blood vessels of pancreatic NETs without off-target vascular or parenchymal toxicity to normal organs.…”
Section: Significancementioning
confidence: 99%
“…SRS with 111 In-DPTA-SPECT/CT has also been compared to 18 F-FDG-PET/CT in studies[81, 82, 86]. Similar, although less dramatic results compared with those seen with the comparison of 68 Ga-DOTA-PET/CT and 18 F-FDG-PET/CT reviewed above, were obtained.…”
Section: Molecular Imaging Of Neuroendocrine Tumorsmentioning
confidence: 69%
“…In one study patients with a positive 18 F-FDG-PET/CT with a SUV ratio of 2.5 of greater had a 4-yr survival rate of 0%[81]. Furthermore, in a number of studies, some patients with G1/G2 tumors had positive 18 F-FDG-PET/CT uptake which had important predictive value[33•, 77, 82]. A number of studies have concluded that the results of 18 F-FDG-PET/CT and 68 Ga-DOTA-peptide-PET/CT in patients with NETs are complementary in providing different information that is clinically relevant[77, 79, 80].…”
Section: Molecular Imaging Of Neuroendocrine Tumorsmentioning
confidence: 99%